Body- and movement-based interventions with male offenders – a narrative review - Chyle, Fabian (International journal of comparative and applied criminal justice, 2018)
Therapeutic and psychosocial accompaniment of offenders is increasingly being understood as a communal responsibility. Apart from recognised treatment batteries, an increasing amount of body- and movement-based interventions is carried out within the prison environment. Extensive literature searches were performed for this review. From a total of 2908, 23 publications were included. An increase in research interest in body- and movement-based interventions during the past 5 years was observed. Such interventions are being flexibly applied in detention contexts across western countries, transnationally. Effects of emotional nature as well as competence are being described. Body- and movement-based interventions may contribute substantially in the supervision within the prison regime and can be applied in different modalities as well as low- and high-threshold treatments. Scientific development in this field still is rudimentary and thus further research is necessary in order to provide more evidence for modification processes and efficacy from validated studies.